Kedudukan dan Kewenangan Ombudsman Republik Indonesia dalam Mengawasi Penyelenggaraan Pelayanan Publik - Sya’roni, Muhammad Isa (al-Daulah: Jurnal Hukum dan Perundangan Islam, 2015)
Abstract: The establishment of the Ombudsman of the Republic of Indonesia was motivated by a powerful demand of society to realize clean and good governance as well as to improve the protection of the rights of the community of the state actor organizers that does not comply with its legal obligations. The Ombudsman has a strong legal foundation because it is based on the norms of law relating to the protection of law for the people and government oversight contained in the constitution. The position of Ombudsman, according to Law No. 37 year 2008 on the Ombudsman of the Republic of Indonesia is a state institution that has the authority to oversee the implementation of public service. It is independent and has no organic relationship with state agencies and other government agencies. In carrying out its duties and authority, it is free from interference of other powers. The establishment of the Ombudsman as a state institution that has the function of supervising the implementation of the bpublic services in Indonesia is appropriate and not contrary to the principles of the Islamic political jurisprudenceâs supervision, namely the principle of al-amr bi al-maruf wa al-nahy an al-munkar to realize a peace and public order and to minimize the occurrence of human rights, such as the functions held by the wilayat al-mazalim and wilayat al-hisbah within the Islamic state administration.Keywords: Ombudsman, position, authority, organization, public services